The The Implementation of Sharia Pawn To Conform To The Guidance of The Qur'an And As-Sunnah Uses The Instructions And Limitations of Al Qawa'id Al-Fiqiyyah - Ian Rakhamawan Suherli; Fauzan Januri; Ishandawi Ishandawi; Nanang Sobarna (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
The progression of time is inevitable, including all manifestations of dispute, particularly in economics, which encompasses a diverse range of transactions, including pawn transactions. To ensure that pawning aligns with Islamic teachings, examining the pawn procedure's legal aspects through the principles of fiqh is imperative. This paper discusses the four principles of fiqh: asasiyah (fundamental), furu'iyah (branch), kulliyah (general), and khasasi (specific). These principles can be employed in sharia pawn (rahn) practice. Fiqh asasiyah, similar to the principles of maslahat, prioritizes the promotion of benefit and justice in rahn. The comprehensive regulations of furu'iyah can facilitate the implementation of Islamic law in rahn. The regulations governing the terms and conditions of rahn are addressed in the kulliyah rules. At the same time, the khasasi law focuses on specific provisions concerning rahn, such as the types of products that can be used as collateral. The topic encompasses fifteen fiqh laws of rahn, which regulate the pillars, conditions, and regulations of rahn. The principles of fiqh are crucial in ensuring that the implementation of rahn aligns with Islamic sharia and effectively addresses the contemporary challenges associated with rahn due to societal advancements. This text employs descriptive analysis, incorporating prior studies' literary evaluations and data from reference works that delve into sunnah, hadith, pawn, and fiqh rules. By understanding the rules of fiqh, pawning practices can be in accordance with sharia and implemented by companies and individuals in the contemporary era without worrying about usury contamination.